Congenital heart defects: the 10-year experience at a single center. (1st February 2020) - Aydin, Emine; Aypar, Ebru; Oktem, Ahmet; Ozyuncu, Ozgur; Yurdakok, Murat; Guvener, Murat; Demircin, Metin; Beksac, M. Sinan
Abstract: Objective: We aimed to evaluate congenital heart disease (CHD) cases according to EUROCAT subgroup classification that were diagnosed during the prenatal period in our center. Methods: CHDs that were prenatally diagnosed using ultrasonography and confirmed by fetal echocardiography were reviewed over a 10-year period. Subgroup classification was finalized at the post-partum period in terms of the EUROCAT guide 1.3. Congenital heart defect subtypes and obstetric outcomes (gestational week at delivery, birth weight, gender, extracardiac structural abnormalities, karyotype results if performed) were analyzed. Results: The data of 180 cases with CHD were examined. Left ventricular outflow tract obstruction (LVOT) was the most common CHD subtype (57/180; 31.6%), which included 48, five, and four cases of hypoplastic left heart syndrome (HLHS), coarctation of the aorta, and aortic valve atresia/stenosis, respectively. Eighteen pregnancies were terminated; the most common CHD subtype among patients of terminated pregnancies was hypoplastic left heart syndrome (HLHS) ( n  = 7, 38.8%). The most common extracardiac malformations were a single umbilical artery, esophageal atresia, and situs inversus in our study group. Eighteen of the 96 (18.75%) neonates with CHD died during the neonatal period. The most common CHD subtype was HLHS (7/18; 38%) among the newborns who died after birth. Conclusion: Prenatal diagnosis of a CHD and subgroup classification is very important for clinical decision making, including prenatal management, recommendations for termination of the pregnancy, postnatal management of the patient, and for early referral to pediatric cardiology and cardiovascular surgery centers.